2008
DOI: 10.1021/bi801565j
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanism of Catalysis of Iron−Sulfur Cluster Transfer from IscU[2Fe2S] by HscA/HscB Chaperones

Abstract: The HscA/HscB chaperone/cochaperone system accelerates transfer of iron-sulfur clusters from the FeS-scaffold protein IscU (IscU 2 [2Fe2S], holo-IscU) to acceptor proteins in an ATP-dependent manner. We have employed visible region circular dichroism (CD) measurements to monitor chaperonecatalyzed cluster transfer from holo-IscU to apoferredoxin and to investigate chaperone-induced changes in properties of the IscU 2 [2Fe2S] cluster. HscA-mediated acceleration of [2Fe2S] cluster transfer exhibited an absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 26 publications
2
98
0
Order By: Relevance
“…Nevertheless, the effect of the deficiency of atpABCEFGH on Fe-S cluster biogenesis and iron homeostasis appears more significant than its effect on growth. ATP is required to generate a driving force for the CydD glutathione transporter (76,77) and for HscA to transfer a preformed Fe-S cluster to various target apo-proteins (50)(51)(52), consistent with the result that impaired ATP biosynthesis in the atp mutants results in decreased Fe-S enzyme activities. Thus, Fe-S cluster maturation and/or iron homeostasis may be strictly influenced by ATP availability (Fig.…”
Section: Anti-iscusupporting
confidence: 58%
See 1 more Smart Citation
“…Nevertheless, the effect of the deficiency of atpABCEFGH on Fe-S cluster biogenesis and iron homeostasis appears more significant than its effect on growth. ATP is required to generate a driving force for the CydD glutathione transporter (76,77) and for HscA to transfer a preformed Fe-S cluster to various target apo-proteins (50)(51)(52), consistent with the result that impaired ATP biosynthesis in the atp mutants results in decreased Fe-S enzyme activities. Thus, Fe-S cluster maturation and/or iron homeostasis may be strictly influenced by ATP availability (Fig.…”
Section: Anti-iscusupporting
confidence: 58%
“…The scaffold protein IscU receives sulfur directly from the sulfane sulfur on IscS (46,47) to form a [2Fe-2S]/[4Fe-4S] cluster in vitro (48,49). It is proposed that the Fe-S cluster assembled on the IscU scaffold can be incorporated into target proteins with the help of the DnaKJ-like proteins HscA and HscB (50)(51)(52). Analysis of the solution structure has revealed that apo-IscU exists in two different conformations, one structured and the other disordered, which can interconvert (53,54).…”
mentioning
confidence: 99%
“…36). The Saccharomyces cerevisiae cysteine desulphurase complex Nfs1-Isd11, frataxin Yfh1, ferredoxin Yah1 and the scaffold Isu1 were overproduced and purified from E. coli ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The released Fe/S cluster may then be transferred to the mitochondrial monothiol glutaredoxin Grx5 or directly to apoproteins (Chandramouli and Johnson 2006;Bonomi et al 2008). Grx5 possibly serves as an Fe/S cluster transfer protein by transiently coordinating the Isu1-derived [2Fe-2S] cluster between two protein subunits and two protein-bound glutathione molecules (Bandyopadhyay et al 2008b;Shakamuri et al 2012).…”
Section: Biogenesis Of Mitochondrial Fe/s Proteins By the Isc Assemblmentioning
confidence: 99%